Effects of Educational Intervention on Nurses’ Knowledge and Attitude Towards Providing Cervical Cancer Screening Information in Selected Health Facilities in Ibadan, Nigeria (2019)
Cervical cancer is a major cause of death among women especially in developing nations. It can be prevented through screening yet many women are unaware of screening options. Nurses are in vantage position to provide cervical cancer screening (CCS) information and services especially in antenatal clinics. The purpose of this study is to evaluate the effects of an educational intervention (EI) on nurses' knowledge and attitude towards providing CCS information. This quasi-experimental study was conducted in eight health facilities in Ibadan, Nigeria. The facilities were randomly divided into intervention group (IG) and control group (CG). A total of 133 consenting nurses (60 in the IG and 73 in the CG) participated. Baseline data were collected using self- administered questionnaire. The nurses in the IG received the EI and both groups were administered with a post-test questionnaire after 6 months. Data were analysed using chi square and Student's t test at p = 0.05. Nurses' mean age was 41.7 years. Knowledge scores for the IG (11.8 ± 3.3) and CG (11.7 ± 3.3) were comparable at baseline (p = 0.901) but was significantly higher among nurses in the IG (14.63 ± 3.12) than CG (12.7 ± 3.5) at 6 months PI (p=0.01). More nurses in the IG had high level of knowledge than CG. There was no significant difference in their attitude at baseline and at PI. There was a significant association between knowledge and attitude towards providing cervical cancer screening information (p<0.000). Education improved knowledge of nurses on cervical cancer screening. Regular education programmes for nurses may result in improved counselling on major health issues like cancer.